Wakinyan : Lakota religion in the twentieth century - Feraca, Stephen E., 1934- (University of Nebraska Press, 1998)
Wakinyan is an excellent overview of Lakota religious thought and practice, introducing readers to its essential components. Through finely detailed descriptions of rituals and various types of religious figures, Stephen E. Feraca explains the significance of such practices as the Sun Dance, sweat lodge ritual, vision quest, Yuwipi ritual, and peyote use. He also discusses the significance of herbs and religious artifacts and objects and explains the roles and responsibilities of medicine men and other religious practitioners.